Physical, Bioactive and Textural Properties of Oleaster (Elaeagnus angustifolia L.) Fruit from Different Locations in Turkey - Meric Simsek; Özge Sufer (Turkish Journal of Agriculture: Food Science and Technology)
The objective of this study was to evaluate the physical, bioactive and textural properties of oleaster fruits grown in different locations of Turkey. The oleaster fruits were obtained from Aksaray, Niğde and İzmir cities and their crumb and crust parts were analyzed individually and freshly. In terms of color, the crust and crumb of oleaster fruits from İzmir had the darkest color with L* values of 46.81 ± 4.06 and 78.91 ± 4.97 among all tested fruits from different locations, respectively. Total of phenolic (TP), flavonoid (TF) and tannin (TT) content (C) and as well antioxidant activities (AA) of oleaster fruits were determined for the crust and crumb of oleaster fruits. The highest TPC (22.30±1.75 mg gallic acid equivalent/g DM), TFC (16.24±1.49 mg catechin equivalent/g DM) and AA (14.05±0.55 μmol trolox equivalent/g DM) by DPPH were found in the crust of Aksaray oleaster fruits. In addition, the crumb of Aksaray oleaster fruit had the highest TPC (16.44±1.67 mg gallic acid equivalent/g DM) among the crumbs of oleaster fruits from different locations. Furthermore, there was no significant difference among the texture of crust and crumb of oleaster fruits obtained from different locations. Results showed the growing location of oleaster fruits had a significant influence on the physical and bioactive properties of fruits. Also, this study indicated that oleaster fruits were rich in bioactive compounds; therefore, they could be incorporated into foods to design functional foods.